Corporate Social Responsibility: Safety, Health and Enviromental Issues in The Kenyan Oil and Gas Industry - Makone, Francis O. (2009)
As the oil industry in Kenya continues to grow, increased pressure is being placed on these companies to contribute in Corporate Social activities. The concept of CSR in the Kenyan Oil companies has been a topic of great interest. These oil companies have however been found to have a narrow perspective of what CSR entails as they do not identify all their stakeholders in their efforts to be socially responsible. Oil companies in Kenya also have various reasons as to why they come up with CSR activities. These factors range from the fact that oil companies want to comply with government policies to the fact that the companies want to be ethical. Oil companies contribute to their CSR efforts by engaging in activities that are geared to both their employees and to the community. To their employees these companies have set up health benefit schemes and have ensured safe working conditions, while to the community these companies have involved themselves in community projects that are geared towards any needy society. In their quest to engage in CSR activities, these companies have also been faced with various challenges. Some of the biggest challenges identified are the lack of resources by these companies to be able to effectively engage in CSR activities and the lack of support from the other stakeholders to assist the oil companies to meet their CSR targets. Oil companies have however come up with different ways to counteract these challenges. Oil companies are now working in conjunction with other organizations that have a direct impact to the society e.g. NGO‘s, NEMA and even Children Homes to ensure that their contributions actually reach the community. This study will try and identify some of the reasons why corporations in the oil industry are geared towards CSR practices, specifically with interest to Safety, Health and the Environment (S.H.E).